I dati INVALSI per indagare e migliorare l'insegnamento della matematica III Seminario "I dati INVALSI: uno strumento per la ricerca" - Falzetti, Patrizia (INVALSI per la Ricerca, 2021)
Numeracy skill is related to the ability to develop and apply mathematical thinking to solve several problems in everyday life (MIUR, 2012). It is considered, both at national and at international level, one of the key skills for the personal achievement, an active citizenship, the social inclusion, and the lifelong learning. As its importance for the individual's growth, Mathematics teaching and learning process has always been a core issue for studies, research, and trials in order to highlight school best practices and to identify any critical points and possible opportunities for improvement. This volume aims to deepen this topic, by collecting some studies submmitted at III edition of the Seminar "INVALSI data: a research tool" held in Bari from 26th to 28th October 2018. INVALSI data could be a useful tool to strengthen the necessary partnership between researchers and teachers to wonder about Numeracy learning processes and to improve teaching activities."